Analisis Rendahnya Tingkat Motivasi Belajar IPS pada Siswa Kelas 7 MTs Darul Ulum Budi Agung - Ulfa, Syarifah Widya; Siregar, Rizky Ananda; Azzura, Febby; Nst, Fatih Riziq Arzein (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the factors that cause low motivation to learn Social Sciences (IPS) in grade VII students of MTs Darul Ulum Budi Agung. The low motivation of students can be seen from the lack of participation in learning, lack of enthusiasm for the material, and low completion of the assigned tasks. Using a qualitative approach, this study reveals that monotonous learning methods, unconducive learning environments, and lack of student confidence are the main causes of this problem. Data were collected through the process of observation, interviews, and literature studies. The data is analyzed through the process of data reduction, data presentation, and conclusion drawn. The results of this study show that efforts are needed to increase learning motivation. The form of efforts that can be made is the development and use of more varied learning methods, increased support from the learning environment, and increased confidence in students